PENDEKATAN KOMUNIKASI DALAM PENYELESAIAN KONFLIK SOSIAL DAN AGAMA DI NUSANTARA - Agus Susanto (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2018)
This article discusses how to approach communication in the settlement of social and religious conflicts, causes and impacts caused by the conflict. In the discussion of this article revealed that social-culture and religion make our nation vulnerable to conflict, from the eastern end to the western end. Therefore, the issue of social-religious conflict needs to be resolved quickly by various parties. Factors that often lie behind the conflict are the curb of inter-religious adaptation, economic jealousy, narrow fanaticism, lack of knowledge of democracy and faith. While the impact is the disruption of security, the cracking of social relationships, destruction of the order of life, and countless material losses. The most important is the settlement of social and religious conflicts that can be taken is; Abitration, which is immediately terminated by a third party in this case the government and law enforcement apparatus; Mediation, termination of the dispute by a third party but no binding decision is given; Conciliation, attempts to bring together the wishes of the disputing parties to achieve mutual consent; Stalemate, the situation when both opposing sides have a balanced power, then stops at a point not attacking each other; adjudication, resolution of conflicts in the courts by giving priority to the justice and impartial to anyone.